Simple determination and quantification of tofacitinib, a JAK inhibitor, in rat plasma, urine and tissue homogenates by HPLC and its application to a pharmacokinetic study - Kim, Ji Eun; Park, Mun Young; Kim, So Hee (Journal of Pharmaceutical Investigation, 2020)
Purpose: Tofacitinib, a janus kinase (JAK) inhibitor, was developed for the treatment of rheumatoid arthritis. To evaluate its pharmacokinetic characteristics, a simple method of quantifying tofacitinib by high-performance liquid chromatography (HPLC) was developed to estimate its concentrations in rat plasma, urine and tissue homogenates. Methods: Hydrocortisone was used as an internal standard. The mobile phase was an isocratic system of acetonitrile: 10 mM ammonium acetate, pH 5.0 (30.5:69.5, v/v), and the flow rate was 1.0 mL/min. Chromatograms were monitored by a UV detector at 287 nm. The retention times for tofacitinib and hydrocortisone were 7.21 and 11.3 min, respectively. Results: The lower limits of quantification for tofacitinib in rat plasma and urine were 0.01 and 0.1 μg/mL, respectively. The intraday assay precisions (coefficients of variation) were generally low; 3.69–5.88% for rat plasma and 4.21–6.18% for rat urine. The corresponding values of interday assay precisions were 5.06% and 5.46%, respectively. Accuracies ranged from 92.9 to 107%, with no interference by endogenous substances. Tofacitinib has a short half-life (39.0 min) and was widely distributed in rat tissues. Conclusion: This HPLC method is very simple and sensitive and can be applied to future preclinical and clinical investigations of tofacitinib.
Keywords: HPLC; JAK 3 inhibitor; Pharmacokinetics; Tofacitinib; Validation